2018
DOI: 10.1007/s00034-018-0844-2
|View full text |Cite
|
Sign up to set email alerts
|

FPGA-Based Real-Time Implementation of Bivariate Empirical Mode Decomposition

Abstract: A Field Programmable Gate Array (FPGA) based parallel architecture for the real-time and online implementation of the bivariate extension of the empirical mode decomposition (EMD) algorithm is presented. Multivariate extensions of EMD have attracted significant attention in recent years owing to their scope in applications involving multichannel and multidimensional data processing, e.g. biomedical engineering, condition monitoring, image fusion. However, these algorithms are computationally expensive due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…The highest sampling and clock rate obtained by the method (FPGA-based) proposed by us is 50 MHz. The sampling rate of our proposed method is higher than the methods proposed in Hong et al 18 and Malik et al 23 Cagdas et al 12 and Chen et al 16 did not mention their sampling rate. The sampling rate is important because the greater the sampling rate, the higher the frequency in a signal the design is able to process (fs ≥ 2fm, fs is the sampling frequency and fm is the maximum frequency of the signal).…”
Section: Results Comparison With Some Existing Methodsmentioning
confidence: 57%
See 2 more Smart Citations
“…The highest sampling and clock rate obtained by the method (FPGA-based) proposed by us is 50 MHz. The sampling rate of our proposed method is higher than the methods proposed in Hong et al 18 and Malik et al 23 Cagdas et al 12 and Chen et al 16 did not mention their sampling rate. The sampling rate is important because the greater the sampling rate, the higher the frequency in a signal the design is able to process (fs ≥ 2fm, fs is the sampling frequency and fm is the maximum frequency of the signal).…”
Section: Results Comparison With Some Existing Methodsmentioning
confidence: 57%
“…The sampling rate is important because the greater the sampling rate, the higher the frequency in a signal the design is able to process (fs ≥ 2fm, fs is the sampling frequency and fm is the maximum frequency of the signal). The sampling frequency in case of Malik et al 23 was 25 MHz, whereas in our case, sampling frequency is 50 MHz, which means our design can process higher frequency signals. The execution time of the design (using STI) proposed in Hong et al 18 and Chen et al 16 is more than the execution time of our proposed design using LBC (same functionality as STI).…”
Section: Results Comparison With Some Existing Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…The motivation behind the use of this criterion is its simplicity and can be used in EMD for its real‐time implementation. It is observed that S varies between 3 and 5 to produce a good IMF [17, 18]. (ii) Here, we have used two envelope generation techniques one with CSI and other one is using ST interpolation (STI) followed by a moving average (MOVAVG) module.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation behind the use of this criterion is its simplicity and can be used in EMD for its real‐time implementation. It is observed that S varies between 3 and 5 to produce a good IMF [17, 18].…”
Section: Introductionmentioning
confidence: 99%